Secondary bonding in dimethylbis(morpholine-4-carbodithioato-κ2 S,S′)tin(IV): crystal structure and Hirshfeld surface analysis - Zaldi, N.; Hussen, R.S.D.; Lee, S.M.; Halcovitch, N.R.; Jotani, M.M.; Tiekink, E.R.T. (International Union of Crystallography, 2017)
The title compound, [Sn(CH3)2 (C5H8NOS2)2], has the SnIV atom bound by two methyl groups which lie over the weaker Sn-S bonds formed by two asymmetrically chelating dithiocarbamate ligands so that the coordination geometry is skew-Trapezoidal bipyramidal. The most prominent feature of the molecular packing are secondary Sn⋯S interactions [Sn⋯S = 3.5654 (7) Å] that lead to centrosymmetric dimers. These are connected into a three-dimensional architecture via methylene-C-H⋯S and methyl-C-H⋯O(morpholino) interactions. The Sn⋯S interactions are clearly evident in the Hirshfeld surface analysis of the title compound along with a number of other intermolecular contacts.